2021
DOI: 10.1177/1357633x211024108
|View full text |Cite
|
Sign up to set email alerts
|

A nurse-led, telehealth-driven hepatitis C management initiative in regional Victoria: Cascade of care from referral to cure

Abstract: Introduction Elimination of hepatitis C virus stands as an unresolved World Health Organization target, and is associated with complications including cirrhosis and hepatocellular carcinoma. Hepatitis C virus management has been revolutionised following the widespread availability of direct-acting antiviral agents in Australia since 2016; however, large proportions of the population remain untreated. Telehealth-based service delivery is an accessible and effective alternative, and we aimed to assess qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Eleven articles report on HCV treatment outcomes through telehealth (Table 1), including remote specialist consultation, educational videos, and the support of primary care providers (five video telemedicine cases, four remote specialist consultations through teleconferences, one telephone consultation, and one paper-based referral followed by a fax or verbal discussion) [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Hcv Treatment Outcomesmentioning
confidence: 99%
“…Eleven articles report on HCV treatment outcomes through telehealth (Table 1), including remote specialist consultation, educational videos, and the support of primary care providers (five video telemedicine cases, four remote specialist consultations through teleconferences, one telephone consultation, and one paper-based referral followed by a fax or verbal discussion) [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Hcv Treatment Outcomesmentioning
confidence: 99%
“…Several studies have shown that virtual visits typically reduce carbon emissions by 40%-70%, while maintaining high quality of care. [9][10][11] Telemedicine reduces the carbon footprint due to reduced travel, but perhaps also because of reduced unnecessary testing. In addition, it may improve access to care for patients who live remotely or are less able to afford a visit in person.…”
Section: Telemedicinementioning
confidence: 99%
“…In this article, we have examined how telehealth affects treatment relationships in hepatitis C, building on existing literature that focuses on patient experience and drawing on qualitative data from interviews with patients and practitioners during the COVID‐19 pandemic in Australia. Overall, the argument contributes novel insights into patient experiences of telehealth for hepatitis C, raising questions about, and adding complexity to, research that emphasises the positive effects of telehealth for patients (Bensted et al., 2021 ; Lepage et al., 2020 ; Rodrigues et al., 2021 ; Schulz et al., 2020 ) by focussing on its role in treatment relationships.…”
Section: Conclusion: Negotiating Proper Distance In Changing Health‐c...mentioning
confidence: 99%
“…While studies have long shown the importance of a positive patient‐practitioner relationship in treatment outcomes and attitudes to health care among people living with hepatitis C (Körner, 2010 ; Zickmund et al., 2004 ), research on patient experiences of telehealth is limited, and is mainly quantitative in methods (Bensted et al., 2021 ; Lepage et al., 2020 ; Rodrigues et al., 2021 ; Schulz et al., 2017 , 2020 ). Few studies have explored in detail how telehealth has shaped health care for people with hepatitis C. This article explores, for the first time, the impact of telehealth on the relational ethics of health care for hepatitis C. As we will argue, the concept of proper distance shows how communications media/technologies affect relationships and, therefore, notions and practices of responsibility.…”
Section: Introductionmentioning
confidence: 99%